Effects of secondary combustion in a gas turbine on the microstructural evolution, mechanical properties, and failure mechanism of the blades. (September 2022) - Khani Moghanaki, Saeed; Kazempour Liasi, Hassan; Mohammadi, Hamidreza; Nasrollahnejad, Farzaneh
Highlights: The gas turbine blade microstructure is investigated after secondary combustion. Dissolution and reprecipitation of γ' particles occurs during secondary combustion. The blades experience temperatures beyond 1280 °C during secondary combustion. Interdendritic fracture surfaces appear in the damaged blades. Abstract: Secondary combustion in a power plant gas turbine occurs when liquid fuel is collected after shutdown or unsuccessful start-up and, for some reasons, was not drained. The pool of liquid is ignited by hot gases during a subsequent start. This uncontrolled combustion causes explosion and the turbine blades suffer very high temperature short exposure that leads to extensive blade damage. In the present research, the effect of very high temperature short exposure on microstructural evolutions and mechanical properties, which occurs during secondary combustion, has been investigated. The microstructure of the blades was evaluated by field emission scanning electron microscope (FESEM). The mechanical properties of the blades were investigated by room temperature and high temperature tensile test and hardness test. The results showed that both primary and secondary γ' particles were dissolved during secondary combustion and then reprecipitated after the turbine trip. Dissolution and reprecipitation phenomena occurred in the upper area of the blade airfoil section. This dissolution of γ' particles led to deterioration of mechanical properties during secondary combustion and ultimately, extensive blades failure. Furthermore, the MC carbide degeneration into M23 C6 and η phase was also observed in the microstructure which was attributed to the increase in temperature during secondary combustion. The hardness of the damaged blade was not uniform along the longitudinal direction of the blade due to the microstructural evolution. The fracture surface of the damaged blades indicated that cracks were propagating along the interdendritic regions.